SURFACE DETERIORATION OF GIC TYPE II BASED ON ITS EXPIRATION DATE AFTER IMMERSION IN CARBONATED DRINK - Muhammad Dian Firdausy (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Inside the oral cavity, restoration always in contact with wet condition, including carbonated drink with low pH level and erosive potential. Sometimes, materials are stored for prolonged time exceeding their expiration date. This research aimed to determine the eﬀect of expiration date (ED) of GIC type II toward its surface deterioration (surface hardness and roughness) when immersed in carbonated drink.Method: This was an experimental laboratory using GIC type II with ED of 2014,2016 and 2021. Ten cylindrical specimens per group were made (d=10mm, h=2mm). Surface hardness and roughness measurements were done prior andafter specimens were immersed for seven days in carbonated drink. Carbonateddrinks were changed daily to maintain its pH level.Result: There were reduction in surface roughness and increased in surfaceroughness after immersed for seven days. The greatest deterioration occurred ingroup expired in 2014. Based on the Kruskal Wallis test result, there was a signifcant diﬀerence in surface hardness alteration (p=0.000) and surface roughness alteration (p=0.000) based on its ED.Conclusion: ED has great impact on surface characteristics (hardness androughness). Using expired GIC type II deal with great risk of surface deterioration when in contact with low pH level beverages